Calculus Detection Calibration Among Dental Hygiene Faculty Members Utilizing Dental Endoscopy: A Pilot Study - Partido, Brian B.; Jones, Archie A.; English, Dana L.; Nguyen, Carol A.; Jacks, Mary E. (Journal of dental education, 2015)
Dental and dental hygiene faculty members often do not provide consistent instruction in the clinical environment, especially in tasks requiring clinical judgment. From previous efforts to calibrate faculty members in calculus detection using typodonts, researchers have suggested using human subjects and emerging technology to improve consistency in clinical instruction. The purpose of this pilot study was to determine if a dental endoscopy‐assisted training program would improve intra‐ and interrater reliability of dental hygiene faculty members in calculus detection. Training included an ODU 11/12 explorer, typodonts, and dental endoscopy. A convenience sample of six participants was recruited from the dental hygiene faculty at a California community college, and a two‐group randomized experimental design was utilized. Intra‐ and interrater reliability was measured before and after calibration training. Pretest and posttest Kappa averages of all participants were compared using repeated measures (split‐plot) ANOVA to determine the effectiveness of the calibration training on intra‐ and interrater reliability. The results showed that both kinds of reliability significantly improved for all participants and the training group improved significantly in interrater reliability from pretest to posttest. Calibration training was beneficial to these dental hygiene faculty members, especially those beginning with less than full agreement. This study suggests that calculus detection calibration training utilizing dental endoscopy can effectively improve interrater reliability of dental and dental hygiene clinical educators. Future studies should include human subjects, involve more participants at multiple locations, and determine whether improved rater reliability can be sustained over time.